Ibrutinib versus bendamustine plus rituximab for first-line treatment of 65 or older patients with untreated chronic lymphocytic leukemia without del(17p)/TP53 mutation in China: a lifetime economic research study - Yuan Hong; Xichuang Chen; Yuanquan Hong; Xingfang Xiao; Yan Wang; Xiaohong You; Jingyi Mi; Tao Zhou; Panpan Zheng; Zhihu Huang (BMC Health Services Research, 2023)
Abstract Background The incidence and mortality rates of patients with chronic lymphocytic leukemia (CLL) in China have recently increased. This study performed a long-term economic evaluation of the first-line treatment strategies ibrutinib (IB) or bendamustine (BE) plus rituximab (RI) for previously untreated older patients with CLL without the del(17p)/TP53 mutation in China. Methods Based on clinical data from large, randomized trials, a Markov model including four disease states (event-free survival, treatment failure, post-treatment failure, and death) was used to estimate the incremental costs per quality adjusted-life year (QALY) gained from the first-line IB strategy versus the BE plus RI strategy over a 10-year period. All costs were adjusted to 2022 values based on the Chinese Consumer Price Index, and all costs and health outcomes were discounted at an annual rate of 5%. Sensitivity analysis was performed to confirm the robustness of base-case results. Results Compared to the first-line BE plus RI strategy, first-line IB treatment achieved 1.17 additional QALYs, but was accompanied by $88,046.78 (estimated in 2022 US dollars) in decremental costs per patient over 10 years. Thus, first-line treatment with IB appeared to have absolute dominance compared to the BE plus RI strategy. Sensitivity analysis confirmed the robustness of these results. Conclusions The first-line treatment with IB is absolutely cost-effective compared to the first-line BE plus RI treatment strategy for 65 or older patients with CLL without the del (17p)/TP53 mutation from the Chinese payer perspective. Therefore, it is strongly recommended that Chinese health authorities select the former strategy for these CLL patients.